Prevalencia de factores desencadenates al desarrollo de la recesión gingival en los usuarios de la Clínica Odontológica de la Universidad Nacional de Loja - Romero Elizalde, Darío Xavier (2016)
The current study was developed to determine the presence of gingival recession and its relationship with the triggers for the age and the sex of users. The observation method was used and the observation guide was the instrument, which allowed us to evaluate and determine the classes where users are located according to Dr. Miller’s classification, triggers were analyzed, such as bacterial plaque, dental calculus, age and sex; all these factors are important because the recession is still a serious oral health issue, and its progress leads to teeth loss. The sample was represented for 62 users, in a large percentage by patients between 35 to 49 years old, which represents 40% of the observed sample; it was also observed the relationship among the age and the Class of gingival recession which showed 56.6% in Class II in the group from 36 to 49, in Class I 45.9% in the group from 18 to 35 years old, and 71.4% in Class III in the group from 50 to 90 years old. According to Miller’s classification, the one with larger presence was Class I, which represents 60% of the sample and the Class with shorter presence was Class III which represents 11% of the sample; the Class III that represented 29%; and the Class IV with a percentage of 0. According to the presence of dental calculus, 46% of the users show supragingival calculus, while 54% shows subgingival and supragingival calculus in the same user. Keywords: Gingival Recession, triggers, Miller’s Classification.